A commentary on evidence-based parenting programs: Redressing misconceptions of the empirical support for Triple P. - Sanders, M.; Pickering, J.; Kirby, J.; Turner, K.; Morawska, A.; Mazzucchelli, Trevor; Ralph, A.; Sofronoff, K. (BioMed Central Ltd., 2012)
A meta-analytic review of the Triple P-Positive Parenting program by Wilson et al., recently published in BMC Medicine, claimed to demonstrate that although Triple P is widely disseminated and adopted, the evidence attesting to the effectiveness of the program is not as convincing as it may appear. Although this review addresses the important issue of evaluation and reporting methods within evidence-based interventions, we contend that the Wilson et al. review contains a number of significant conceptual, methodological and interpretational inadequacies that render the key conclusions of their review problematic.